DIGITALIZATION AS A TREND IN THE DEVELOPMENT OF AGRICULTURE IN THE CONDITIONS OF A NEW TECHNOLOGICAL WAY - Murodjon Berdimurodov Baxodir o'g'li (Scholar Express Journals, 2022)
Digitalization allows expanding the capabilities of the agricultural sector (including agricultural production), increasing the efficiency of resource use. With its help, the efficiency of agricultural production is increased due to the optimal planning of the structure of crops, automation of irrigation and nonfodder feeding of plants, digital modeling of crop yields, and optimization of the feed ration of farm animals. However, domestic agriculture, which is in dire need of new sources of labor productivity growth, has so far made little use of these opportunities. The main reasons are the high cost of introducing digital technologies into production and the lack of skills and competencies for workers to work with digital technologies. The analysis of the level of digitalization of agriculture in Uzbekistan has been carried out. The main problems hindering the development of digital agriculture in our country are identified, one of which is human capital. Based on a survey of students from different faculties of the branch university, the main competencies were identified, which, in their opinion, will be in demand in farms using digital technologies. A list of skills and competencies that will become the main ones for the implementation of production in the conditions of digital agriculture is proposed
Keywords: Digitalization; agriculture; human capital; competencies